Lian Hua Qing Wen Capsules, a Potent Epithelial Protector in Acute Lung Injury Model, Block Proapoptotic Communication Between Macrophages, and Alveolar Epithelial Cells - Li, Qi; Ran, Qingsen; Sun, Lidong; Yin, Jie; Luo, Ting; Liu, Li; Zhao, Zheng; Yang, Qing; Li, Yujie; Chen, Ying; Weng, Xiaogang; Wang, Yajie; et al. (Frontiers in Pharmacology, 2020)
Besides pathogen evading, Acute Lung Injury (ALI), featuring the systematic inflammation and severe epithelial damages, is widely believed to be the central non-infectious factor controlling the progression of infectious diseases. ALI is partly caused by host immune responses. Under the inspiration of unsuccessful treatment in COVID-19, recent insights into pathogen–host interactions are leading to identification and development of a wide range of host-directed therapies with different mechanisms of action. The interaction unit consisting of macrophages and the alveolar epithelial cells has recently revealed as the therapeutic basis targeting ALI. Lian Hua Qing Wen capsule is the most effective and commonly-used clinical formula in treating respiratory infection for thousands of years in China. However, little is known about its relevance with ALI, especially its protective role against ALI-induced alveolar tissue damages. Aiming to evaluate its contribution in antibiotics-integrating therapies, this study pharmacologically verified whether LHQW could alleviate lipopolysaccharide (LPS)-induced ALI and explore its potential mechanisms in maintaining the physiology of macrophage-epithelial unit. In ALI mouse model, the pathological parameters, including the anal temperature, inflammation condition, lung edema, histopathological structures, have all been systematically analyzed. Results consistently supported the effectiveness of the combined strategy for LHQW and low-dose antibiotics. Furthermore, we established the macrophages-alveolar epithelial cells co-culture model and firstly proved that LHQW inhibited LPS-induced ER stress and TRAIL secretion in macrophages, thereby efficiently protected epithelial cells against TRAIL-induced apoptosis. Mechanistically, results showed that LHQW significantly deactivated NF-κB and reversed the SOCS3 expression in inflammatory macrophages. Furthermore, we proved that the therapeutic effects of LHQW were highly dependent on JNK-AP1 regulation. In conclusion, our data proved that LHQW is an epithelial protector in ALI, implying its promising potential in antibiotic alternative therapy.